A carne mais barata do mercado é a carne negra: um estudo com histórias de vida de trabalhadores industriais negros - Matheus Arcelo Fernandes Silva (2018)
This dissertation aimed the analysis and comprehension of how racial relations are manifested and experienced by black industrial workers, based on their life histories. Using a qualitative approach, the study relied on life histories narrated by two black workers, Leila and Clovis. The perspective adopted for the life histories was the psycho-sociology, which is not an individualizing theory, because it considers social aspects that permeate relations between individuals and mark their lives from dialectical mediations. Thus, it is not possible to say that it is a structural perspective, insofar as the individual also changes the structure, just as it is possible that the structure influences it (BARROS; LOPES, 2013). As a complementary form, these narratives were categorized and analyzed with the french approach of discourse analysis which does not fail to consider the social conditions of production nor the ideological aspects presents in the discourses (FIORIN, 2005). The idea defended is that racism is a structural element, which does not only represent a moral and individualistic dysfunction, but presents itself in a distinct way in the life of the black people, who mediate in relation to the theme. As Gonzalez (1984) points out, when inquiring about how we arrived at this scenario of racial discrimination, its stand out that we never really left it, so it is important to understand the socio-historical elements that marked the construction of race relations in Brazil. In addition, understanding the specificities of racism in Brazil demonstrates its often perverse character from the denial of a scenario of racial inequalities, especially from the myth of racial democracy. The research results reinforce the growing need for racial debate in Brazil and the need to think about articulated discrimination elements, as well as the possibilities that the use of life histories could represent